Kesenjangan Digital dan Kompetensi Digital Mahasiswa Akuntansi - Weli; Mukhlasin, Mukhlasin; Sjarief, Julianti; Madyakusumawati, Synthia (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The problem of this research is the existence of a digital divide among accounting students in Indonesia despite the rapid growth of the digital economy in Southeast Asia. This research explores the relationship between the digital divide, seen through social factors, and the digital competence of accounting students. This research uses a quantitative approach, with the subjects being accounting students. Data was collected through a survey with a questionnaire distributed to 398 accounting students at various universities in Indonesia. Data analysis was carried out using descriptive tests and non-parametric tests. The research results show that social factors significantly influence students' digital access and competence. Younger students tend to have higher levels of digital competency. Family factors such as parental education, employment, and income significantly influence students' digital abilities. In addition, computer ownership by students and effective technology integration by lecturers also impact students' digital competence. In conclusion, the digital divide still exists among accounting students in Indonesia, which affects their digital competence. The implications of this research include the need for curriculum expansion and social interventions to overcome the digital divide among accounting students, ensuring their readiness to face the digital era.